Personality predictive analysis based on artificial neural network - Zuriani, Mustaffa; Nur Alia Shahira, Mohd Zaidi; Ernawan, Ferda; Elhadi, Haithm; Hakim, Muhammad Malik (Institute of Electrical and Electronics Engineers Inc., 2022)
Individual personality is a vital criterion in a human life as well as in a development of an organization. Every individual holds a different personality type with various characteristics in terms of thinking, feeling, and behaving. Due to that matter, analyzing human personality should be done carefully which can be challenging and time consuming. Therefore, this study presents a personality prediction model based on Artificial Neural Network (ANN). The prediction was realized on the Big Five personality model. The dataset consists of 709 rows and retrieved from open-source website called Kaggle. For training, validation and testing phases, the dataset was divided into 70:15:15 respectively. Findings of the study demonstrated the capability of ANN in producing better accuracy compared to three identified algorithms which includes Naïve Bayes, ZeroR and Random Forest.